2023
DOI: 10.1177/11786221231214350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grass Components on the Temporal Response of Surface Soil Water to Precipitation and Air Temperature in the Loess Plateau

Jianbo Liu,
Guangyao Gao,
Weiliang Chen
et al.

Abstract: The Loess Plateau of China is facing increasingly serious challenges related to water shortage issues despite the successful vegetation restoration. Surface soil water (0–40 cm) is crucial to water transfer and discharge in the soil-plant-atmosphere continuum, which is controlled by precipitation (P), air temperature (Ta), and plant components. This study selected one typical grass species and set different treatments of natural condition (NC), removing litter (CR), and only roots (OR), to analyze the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Through an analysis of the processes (infiltration, loss and retention) of soil water storage, we found that the final order of the rainwater retention rate was NC (26.43%) > OR (13.71%) > CR (4.58%) in sub-shrub land, which differs from that in grassland [38]. The roots were useful for soil water conservation during the whole growing season, the canopy showed a negative effect on conserving soil water since it depleted the increased amount of infiltration derived from the roots, and the litter generally improved soil water by offsetting the water depletion of the canopy.…”
Section: Response Of Soil Water Storage Processes To Sub-shrub Compon...mentioning
confidence: 91%
See 1 more Smart Citation
“…Through an analysis of the processes (infiltration, loss and retention) of soil water storage, we found that the final order of the rainwater retention rate was NC (26.43%) > OR (13.71%) > CR (4.58%) in sub-shrub land, which differs from that in grassland [38]. The roots were useful for soil water conservation during the whole growing season, the canopy showed a negative effect on conserving soil water since it depleted the increased amount of infiltration derived from the roots, and the litter generally improved soil water by offsetting the water depletion of the canopy.…”
Section: Response Of Soil Water Storage Processes To Sub-shrub Compon...mentioning
confidence: 91%
“…The litter is beneficial as it shelters the soil to reduce soil evaporation and reduces soil water loss from solar radiation; meanwhile, it also improves soil properties to increase infiltration and reduce runoff. The roots provide channels for water infiltration [38,39]. Consequently, different components have different functions in soil water infiltration or loss.…”
Section: Field Experimentsmentioning
confidence: 99%